Agile transformation by organisational development projects - Bushuyev, S. D.; Bushuiev, D. A.; Bushuieva, V. B.; Bojko, O. O. (Національний технічний університет "Харківський політехнічний інститут", 2020)
The organisationl development of project, programs and project portfolios management systems with drivers of agile transformation is considered. Fust changes in the environment require further research into the effectiveness of the application of existing agile methodologies, knowledge systems and competencies of project managers and their leadership. The foundations of environmental change lie in changing the decision-making paradigm in agile project and programs management. The article explores modern approaches to leadership formation when applying agile methodologies of its specificity from decision-making processes in project management. The problems of leadership creation and development in the application of agile project management methodologies for the implementation of Agile transformation of organisation are considered. The studies were conducted based on a competency-based approach modelled by the International Project Management Association. The content model of competency of the leader applying agile management is presented. The Agile leadership and leadership behaviour patterns are formed in a project management behavioural competency system based on agile technology methods and tools. These competencies included: Self-reflection and self-management, Personal integrity and reliability, Personal communication, Relationships and interaction, Leadership, Teamwork, Conflicts and Crises, Resourcefulness, Negotiation, and Orientation to results. The patterns of project managers' behaviour as agile leaders in project product creation and agile project management are explored. The differences in the behaviour patterns of leaders and agile leaders were examined by behavioural competencies within the identified key competency indicators. Such patterns allowed the authors to identify bottlenecks in the application of agile project management methodologies in the context of the development for Agile transformation of organization.

Розглянуто проєкти, програми і системи управління портфелями проєктів організаційного розвитку, які є драйверами гнучких перетворень. Швидкі зміни середовища вимагають подальших досліджень ефективності застосування існуючих Agile (гнучких) методологій, систем знань і компетенцій керівників проєктів і керівництва організацій. Основи змін навколишнього середовища лежать в зміні парадигми прийняття рішень в гнучкому управлінні проєктами та програмами. У статті досліджено сучасні підходи до формування лідерства при застосуванні Agile методологій його специфіки в процесах прийняття рішень з управління проєктами. Розглянуто проблеми створення та розвитку лідерства в застосуванні Agile методологій управління проєктами для Agile трансформації організацій. Дослідження проводилися на основі компетентнісного підходу, запропонованого Міжнародною асоціацією управління проєктами. Представлена змістовна модель компетентності лідера, який застосовує Agile менеджмент. Моделі поведінки Agile лідерства формуються в системі поведінкової компетентності управління проєктами, яка заснована на методах і інструментах Agile технологій. Ці компетенції включали: саморефлексію і самоврядування, особисту цілісність і надійність, особисте спілкування, відносини і взаємодія, лідерство, командна робота, конфлікти і кризи, винахідливість, узгодження і орієнтацію на результати. Досліджено закономірності поведінки керівників проєктів як Agile лідерів у створенні продуктів і гнучкому управлінні проектами. Були досліджені різниці у патернах поведінки традиційних лідерів і Agile лідерів по перспективним і поведінковими компетенціями з застосуванням ключових показників компетентності. Такі патерни дозволили авторам визначити вузькі місця в застосуванні гнучких методологій управління проєктами в контексті Agile трансформації організацій.
Agile трасформація на основі проєктів організаційного розвитку
Keywords: agile transformation; agile project management methodologies; project manager; leadership competences; behaviour pattern; гнучкі трансформації; гнучкі методології управління; лідерські компетенції; моделі поведінки; менеджер проєктів; управління проєктами